Searching for Minimum in Dependence of Squared Speed-of-Sound on Collision Energy - Fu-Hu Liu; Li-Na Gao; Roy A. Lacey (Advances in High Energy Physics)
Experimental results of the rapidity distributions of negatively charged pions produced in proton-proton (p-p) and beryllium-beryllium (Be-Be) collisions at different beam momentums, measured by the NA61/SHINE Collaboration at the super proton synchrotron (SPS), are described by a revised (three-source) Landau hydrodynamic model. The squared speed-of-sound parameter cs2 is then extracted from the width of rapidity distribution. There is a local minimum (knee point) which indicates a softest point in the equation of state (EoS) appearing at about 40A GeV/c (or 8.8 GeV) in cs2 excitation function (the dependence of cs2 on incident beam momentum (or center-of-mass energy)). This knee point should be related to the searching for the onset of quark deconfinement and the critical point of quark-gluon plasma (QGP) phase transition.